Study of air pollution from vehicle emissions at R.T.A. Milono – Willem A. S. intersections Palangka Raya City - Permana, Ari Widya; Tawaqal, Gusti Iqbal (Jurnal Teknika, 2025)
The intersection of R.T.A. Milono Road and Willem A. Samad Road is one of the busiest three-arm signalized intersections in Palangka Raya. There is a significant amount of traffic at this intersection, particularly during rush hour when people are commuting to work, school, and college. Exhaust emissions from the high volume of traffic are generated by numerous vehicle movements. These vehicle exhaust emissions negatively impact the environment and human health. To compare the quantity of exhaust emissions at the intersection with national ambient air quality standards based on government regulations, this study first calculates the amount of exhaust emissions from motor vehicles. The study employs an empirical calculation formula and a survey of vehicle speed and traffic volume. Based on the analysis of vehicle emissions compared with national air quality standards, it was found that Willem A. Samad Road meets the permitted quality standards for all types of pollutants. Meanwhile, R.T.A. Milono (A) Road and R.T.A. Milono (B) Road meet the standards for NO2 pollutants (below 200 µg/m³) and PM10 pollutants (below 72 µg/m³) but exceed the permitted standards for CO pollutants (above 4,000 µg/m³) and HC pollutants (above 160 µg/m³).